The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/agj2.20316
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a wider row spacing and recommended nitrogen in no‐till wheat

Abstract: The optimal row spacing aims to maximize profitability by balancing the reduction in production costs from a wider row spacing against a potential decline in yield and increased weed pressure. A wider row spacing should increase area seeded per day, improve residue flow around seeder openers and the success of seeding between stubble rows. This study investigated the feasibility of a wider row spacing by studying the effects of row spacing (25, 30, 35, 40 cm) and N fertilizer rates (20, 40, 80, 120, 160 kg N h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
5
3
0
Order By: Relevance
“…For each crop, the highest yields occurred at 100% N rate with the exception of flax, which had the highest yield, 1.26 t ha −1 , at 60% N followed by a slight numerical decrease in yield, 1.25 t ha −1 , at 100% (Figure 2). The highest yields occurring at 100% recommended N coincides with past studies (May et al., 2010; May, Aldous, & Lafond, 2020). Yield increased from 20 to 100% N regardless of the presence of medic; however, there was a larger difference in yield between N rates in the nonmedic treated plots than the medic plots, 0.46 t ha −1 (Figure 3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For each crop, the highest yields occurred at 100% N rate with the exception of flax, which had the highest yield, 1.26 t ha −1 , at 60% N followed by a slight numerical decrease in yield, 1.25 t ha −1 , at 100% (Figure 2). The highest yields occurring at 100% recommended N coincides with past studies (May et al., 2010; May, Aldous, & Lafond, 2020). Yield increased from 20 to 100% N regardless of the presence of medic; however, there was a larger difference in yield between N rates in the nonmedic treated plots than the medic plots, 0.46 t ha −1 (Figure 3).…”
Section: Resultssupporting
confidence: 92%
“…Oat had a tiller density of 313 m −2 , while wheat had a tiller density of with 387 m −2 . Previous research also found that increasing the N rate increased tiller density in oat and wheat (May, Aldous, & Lafond, 2020; May, Brandt, & Hutt‐Taylor, 2020). The year × medic × crop interaction accounted for 41% of the variance of the random effects (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the combined analysis, narrower rows increased total crop biomass at maturity (+2.1 Mg ha −1 ) with interactions being only of magnitude (Table 2). The consistent effect of narrower row spacing on total crop biomass is similar to other reports (Chen et al., 2008; Marshall et al., 1987; May et al., 2020).…”
Section: Resultssupporting
confidence: 91%
“…This difference may be due to higher panicle density obtained by the previous study at a low N rate 465 panicles m -2 compared to the 407 panicles m -2 at a low N rate in this study so less N was required in the previous study to maximize panicle density. The increase in panicle or head density as the N rate increased has been observed in other small grains under similar environmental conditions including oat, wheat and barley (May et al 2020a(May et al , 2020bO'Donovan et al 2015).…”
Section: Plant and Panicle Densitysupporting
confidence: 59%